(untitled) (Research, Society and Development, 2023)
Introduction: COVID-syndrome presents itself as a post-systemic state with symptoms and the development of possible late sequelae after the acute disease state has subsided. Among these sequelae, cardiac magnetic resonance imaging (CMR) findings are associated with the potential outcomes in previously infected patients. The athletic population deserves a careful look at all events involved in the physio-metabolic process that can culminate in sudden cardiac death. Purpose: To evaluate the prevalence of CMR changes in athletes previously infected with SARS-CoV-2. Methods: Systematic literature review with analytical studies found in PubMed, LILACS, and CENTRAL databases of previous athletes tested for SARS-CoV-2 by CMR testing. Results and review: From six studies selected, most of them reported athletes in CMR, as late gadolinium enhancement, and T2-weighted abnormalities, which showed the presence of subclinical or clinical forms of myocarditis, with a prevalence of variation of 0.12 to 2.3% in relation to the population. In addition, CMR was responsible for diagnosing cases in which there were neither clinical nor strongly suggestive changes to indicate screening for myocarditis. Conclusion: Myocarditis disease is part of the study group of diseases associated with the post-COVID syndrome and, despite the low prevalence, further research is needed to outline the best strategy that is capable of identifying and diagnosing myocarditis, even after mild and moderate cases.